Current Continuing Professional Education Practice among Malaysian Nurses - Mei Chan Chong; Karen Francis; Simon Cooper; Khatijah Lim Abdullah (Nursing Research and Practice)
Nurses need to participate in CPE to update their knowledge and increase their competencies. This research was carried out to explore their current practice and the future general needs for CPE. This cross-sectional descriptive study involved registered nurses from government hospitals and health clinics from Peninsular Malaysia. Multistage cluster sampling was used to recruit 1000 nurses from four states of Malaysia. Self-explanatory questionnaires were used to collect the data, which were analyzed using SPSS version 16. Seven hundred and ninety-two nurses participated in this survey. Only 80% (562) of the nurses had engaged in CPE activities during the past 12 months. All attendance for the various activities was below 50%. Workshops were the most popular CPE activity (345, 43.6%) and tertiary education was the most unpopular activity (10, 1.3%). The respondents did perceive the importance of future CPE activities for career development. Mandatory continuing professional education (MCPE) is a key measure to ensure that nurses upgrade their knowledge and skills; however, it is recommended that policy makers and nurse leaders in the continuing professional development unit of health service facilities plan CPE activities to meet registered nurses’ (RNs) needs and not simply organizational requirements.